Sporotrichosis successfully treated with terbinafine and potassium iodide: Case report and review of the literature - Coskun, B; Saral, Y; Akpolat, N; Ataseven, A; Çiçek, D (Springer, 2004)
Sporotrichosis is rare in Turkey. We report a 40-year-old woman who had subcutaneous sporotrichosis caused by sporothrix schenckii that was successfully treated with terbinafine (250 mg, twice a day) for a period of 6 months. She received a saturated solution of potassium iodide orally for two months. Terbinafine and potassium iodide are suggested to be the agents of choice for treatment of subcutaneous sporotrichosis.
Keywords: sporothrix schenckii; terbinafine; potassium iodide